ANALYSIS OF @ALENAVDS CONTENT STRATEGY IN FASHION PRODUCT MARKETING ON THE TIKTOK PLATFORM - Octavia, Amanda; Istiqomah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the content strategies used by the TikTok account @alenavds in marketing fashion products, focusing on how content creators influence consumer behavior, particularly among Generation Z, through effective content marketing techniques. Method: A qualitative approach with content analysis was employed, examining video content and the use of TikTok's maximum features, such as unboxing videos, mix & match outfits, and interactive features like the bio link and yellow basket. Results: The findings reveal that @alenavds' content strategy effectively builds a personal brand and fosters closeness with the audience through personal storytelling. This strategy enhances impulsive buying behavior on the platform. Novelty: This research contributes to the understanding of TikTok's role in shaping consumer behavior through content marketing, supporting the relevance of Content Marketing Theory. The study aligns with previous research by Dewi (2023) and Saragih & Andriyansah (2023) on TikTok's promotional effectiveness, offering insights into successful strategies used by fashion influencers and the potential of TikTok Shop as a marketplace. This study highlights the increasing impact of social media platforms in contemporary digital marketing.